PENGARUH KEPEMIMPINAN TERHADAP TECHNOPRENEURSHIP DALAM UMKM MENGGUNAKAN SYSTEMATIC LITERATURE REVIEW - Kurniawan, Irfan; Veri, Jhon (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
In the digital era, the role of leadership in driving technology adoption and innovation in the SME sector is becoming increasingly important. SMEs, which contribute significantly to Indonesia's economy, face challenges in adopting technology amidst global competition. This research examines the influence of leadership on technopreneurship in SMEs using the Systematic Literature Review (SLR) method. Through SLR, this study aims to analyze scientific literature to understand how leadership styles and leader characteristics affect the implementation of technopreneurship in SMEs. The research results show that transformational leadership style, clear vision, openness to change, and the ability to manage risk play important roles in the successful adoption of technopreneurship. This study also reveals the importance of leaders' roles in managing organizational change, building a culture of innovation, and facilitating continuous learning. These findings provide valuable insights for policymakers, business practitioners, and academics to enhance the competitiveness and resilience of Indonesian SMEs through technopreneurship.